Figures of Negativity in Julia Kristeva from “Poetry and Negativity” to Black Sun - Tenev, Darin (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
This paper traces the role negativity played in Kristeva’s writings from the 1960s to the 1980s, i.e. from early texts such as “Poetry and Negativity” through Revolution in Poetic Language and Polylogue to Powers of Horror and Black Sun. On the one hand, negativity allows for a reconstruction of Kristeva’s conceptual development from the early “structuralist” work to her psychoanalytic turn. The paper demonstrates in what way the theorization of negativity opened the way for a new form of engagement with psychoanalysis. On the other hand, negativity helps to recontextualize Kristeva’s conceptions within the broader horizon of her contemporary theoretical scene. Negativity helps to delineate her unique position in the latter vis-à-vis thinkers such as Jean-Paul Sartre, Jacque Derrida, Jean-François Lyotard, Jean-Luc Nancy, etc., and simultaneously vis-à-vis the psychoanalytical work of Jacques Lacan, André Green, and others. The paper also contains a philosophical stake. By rereading and reevaluating Kristeva’s take on negativity it shows in what sense Kristeva’s work poses an ontological question about negativity that is at the same time a question about the possible redefinition of matter.